2000
DOI: 10.1016/s0022-5223(00)70120-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy before surgery for early-stage lung cancer: A novel approach

Abstract: Induction chemotherapy with paclitaxel and carboplatin is feasible and produces a high response rate with acceptable morbidity and mortality rates in early-stage non-small cell lung carcinoma. A prospective randomized trial comparing 3 cycles of induction chemotherapy and surgery with surgery alone in early-stage non-small cell lung carcinoma is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(70 citation statements)
references
References 19 publications
3
64
0
3
Order By: Relevance
“…20 It is also reported that induction chemotherapy with other new drugs produces a high response rate in early stage NSCLC. 21 Therefore, the subjects of our study were limited to pathological Stage I or II NSCLC patients. A quantitative real-time RT-PCR assay is able to determine mRNA levels from nanogram amounts of total RNA, 22 thus, it is possible to measure TS mRNA levels in biopsy specimens obtained with a bronchofiberscope or needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is also reported that induction chemotherapy with other new drugs produces a high response rate in early stage NSCLC. 21 Therefore, the subjects of our study were limited to pathological Stage I or II NSCLC patients. A quantitative real-time RT-PCR assay is able to determine mRNA levels from nanogram amounts of total RNA, 22 thus, it is possible to measure TS mRNA levels in biopsy specimens obtained with a bronchofiberscope or needle biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming DFS rates at 1 year of 70 and 80%, 40 patients per arm were required to correctly select the arm that is not inferior with the probability of 84.9%. The 'minimal' DFS rate of 70% was assumed with the prior report from North America, in which the 1-and 2-year survival rates were reported to be 85 and 56%, respectively (Pisters et al, 2000). The assumption was rough and might well be inaccurate, for no DFS data were available from the literature.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…Recent trials of preoperative platinum-based chemotherapy have reported promising results in c-stage IB/II NSCLC (Pisters et al, 2000;Depierre et al, 2002;Rosell et al, 2002). One advantage of the preoperative chemotherapy is better tolerability and compliance.…”
mentioning
confidence: 99%
“…Although the strongest rationale for the use of the trimodality therapy stems from the promising results of clinical phase II data, upfront systemic chemotherapy offers several practical as well as theoretical advantages (Pisters et al, 2000). Early introduction of systemic therapy may be expected to lead to early control of micrometastases.…”
Section: Rationales For Trimodality Therapymentioning
confidence: 99%
“…However, the compliance rate for this strategy was reported to be poor (Pisters et al, 2000;Rusch et al, 2001). In addition, some deaths related to drug toxicity have also been reported during the consolidation phase (Albain et al, 2005), prompting further questioning of its benefits.…”
Section: Toxicity Of the Chemoradiotherapymentioning
confidence: 99%